Immune Response to Verotoxin 1 and 2 in Children with Escherichia Coli O157:H7 Hemorrhagic Colitis and Classic Hemolytic Uremic Syndrome - François Proulx; Jean P Turgeon; Gilles Delage; Hermy Lior; Lucette Lafleur; Luc Chicoine (Canadian Journal of Infectious Diseases)
Objectives: To compare neutralizing antibody titres against verotoxin (vt)-1 and vt-2 between children with uncomplicated hemorrhagic colitis (hc) and those with classic hemolytic uremic syndrome (hus). vt antibody titres were also compared in children with hc who received trimethoprim-sulfamethoxazole with those who did not.